Campaña de difusión del servicio de envío y recibo de remesas transferencia segura” del banco central del Ecuador - Carriel, Adela (2010)
This project developed a technical market study, marketing plan, administrative and financial study for the analysis of the campaign to publicize the service of sent and receipt of remittances "Transferencia Segura" of Banco Central del Ecuador, therefore be investigated how is the current market within the scope of remittances, observing which are their main advantages and disadvantages, opportunities in the future, etc. Being essential to make a survey in different strategic points of the city, allowing the data obtained are the best, Which ratings will be to develop strategies and insert them into the Marketing Plan, and required to achieve a significant increase in users that know, select and choose this service, using the marketing mix is determined prices, distribution channels and advertising strategies appropriate to achieve the efficient service to be offered. The administrative study will reveal the necessary people that make up the team, about the financial study, to observe the viability of this Diffusion Campaign, analyzing the operations necessary to make this Project work and shows the necessary requirements.